Aero-structural design of bridges focusing on the buffeting response: Formulation, parametric studies and deck shape tailoring. Issue 204 (September 2020) - Cid Montoya, M.; Hernández, S.; Nieto, F.; Kareem, A.
Abstract: The design of long-span bridges under wind places multiple demands that are frequently contradictory in regard to the resulting deck configuration. The structural demand requires that the deck contributes to the bridge stiffness, which results in bluff geometry. Conversely, aeroelastic aspects demand that the deck shape be more streamlined to reduce the aerodynamic and aeroelastic load effects. This requires that the design of long-span bridges be carried out as an aero-structural design problem, where the goal is to obtain designs with the lowest cost that simultaneously fulfill the structural and aeroelastic constraints. This study presents a numerical framework for the aero-structural design of long-span bridges under buffeting focusing on the deck shape. In this paper, the relationship between the buffeting response of a cable-stayed bridge and its deck shape is analyzed by means of parametric studies that help to better understand the role played by each involved parameter. This information is used to tailor the deck shape aiming at keeping the buffeting response under a given threshold. By building upon this framework, the design problem can be recast as an aero-structural optimization problem. Highlights: Design of long-span bridges is tackled from an aero-structural perspective. Systematic shape parametric studies of the bridge buffeting response are reported. Modifications on the deck shape configuration can drastically improve the buffeting performance. A buffeting-resistant deck shape tailoring has been carried out.